The Annual Cycle of Air-Sea Fluxes in the Northwest Tropical Atlantic - Bigorre, Sebastien P.; Plueddemann, Albert J. (Frontiers in Marine Science, 2021)
In this article we analyze eleven years of near-surface meteorology using observations from an open-ocean surface mooring located in the Northwestern Tropical Atlantic (51°W, 15°N). Air-sea fluxes of heat, freshwater and momentum are derived from these observations using the Coupled Ocean–Atmosphere Response Experiment (COARE) bulk parameterization. Using this dataset, we compute a climatology of the annual cycle of near-surface meteorological conditions and air-sea fluxes. These in-situ data are then compared with three reanalyses: the National Centers for Environmental Prediction-Department of Energy (NCEP-DOE (hereafter referred to as NCEP-2)), the European Centre for Medium-Range Weather Forecasts (ECMWF) Interim and the Modern-Era Retrospective analysis for Research and Applications, version 2 (MERRA-2) reanalyses. Products from the Clouds and the Earth's Radiant Energy System (CERES) and the Tropical Rainfall Measuring Mission (TRMM) are also used for comparison. We identify the agreements and characterize the discrepancies in the annual cycles of meteorological variables and the different components of air-sea heat fluxes (latent, sensible, shortwave and longwave radiation). Recomputing the reanalyses fluxes by applying the COARE algorithm to the reanalyses meteorological variables results in better agreement with the in-situ fluxes than using the reanalyses fluxes directly. However, the radiative fluxes (longwave and shortwave) from some of the reanalyses show significant discrepancies when compared with the in-situ measurements. Longwave radiation from MERRA-2 is biased high (too much oceanic heat loss), and NCEP-2 longwave does not correlate to in-situ observations and other reanalyses. Shortwave radiation from NCEP-2 is biased low in winter and does not track the observed variability in summer. The discrepancies in radiative fluxes versus in-situ fluxes are explored, and the potential regional implications are discussed using maps of satellite and reanalyses products, including radiation and cloud cover.